O najbliższym otoczeniu człowieka na przykładzie zielonogórskich urbanonimów = About the nearest human environment on the example of Zielona Góra urbanonyms - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The considerations undertaken in this article concern the role of the immediate surroundings in urbanonymity, primarily in the urban nomenclature of Zielona Góra. This article focuses on city names motivated by various elements from space close to the inhabitants, being both a product of human and nature, also giving an idea of the changing reality. In addition, attention was paid to the changes in the perspective of viewing the nearest human environment over the centuries, recorded in the names of streets in Zielona Góra.
Keywords: onomastyka; urbanonimy; najbliższe otoczenie człowieka; onomastics; urbanonyms; the immediate environment of the human